SENSITIVITY OF ANTIBIOTIC-RESISTANT MICROORGANISMS TO METABOLITES OF LACTOBACTERIA AND COMBINATION OF LACTOBACILLUS RHAMNOSUS GG AND SACCHAROMYCES BOULARDII METABOLITES - Isayenko, O.Yu.; Popov, N.N.; Ryzhkova, T.N.; Kotsar, O.V.; Dyukareva, G.I. (World of Medicine and Biology, 2020)
The study investigates the antibacterial activity of metabolites (cultured separately Lactobacillus rhamnosus GG or in combined with Saccharomyces boulardii in disintegrates of L. rhamnosus GG) against multidrug-resistant microorganisms. Metabolites of lactobacillus and L. rhamnosus with S. boulardii demonstrated a 100 % bactericidal effect on the Corynebacterium xerosis regardless of the initial test culture seeding dose. All the experimental samples were bactericidal on the strains Lelliottia amnigena, Acinetobacter baumannii, Pseudomonas aeruginosa with a lower initial seeding dose (0.5 units by the McFarland scale, diluted 10 times). Increasing the dose of test cultures to 1.0 unit by the McFarland scale was accompanied by the presence of the pathogens viable cells (48.0±8.32 – 68.72±7.16) % after exposure to cell-free substances. The metabolites obtained by means of our own technology, due to its high antibacterial activity against antibiotic-resistant pathogens, open the prospect for further designing a new class of antimicrobial agents for broad spectrum.
Keywords: metabolites; disintegrates; antibiotic-resistant microorganisms; Lactobacillus rhamnosus GG; Saccharomyces boulardii